Development of a Local-Content-Based Interactive Science E-Book in Chemistry Education: Matter and Its Changes Material to Enhance Elementary School Students’ Science Literacy - Nena Puspita Sari; Helmi Suardi; Budi Rizka (Jurnal Penelitian Pendidikan IPA, 2026)
Developing students' scientific literacy requires learning resources that are interactive, contextual, and relevant to their cultural environment. This study aimed to develop and evaluate a local-content-based interactive science e-book on the topic of matter and its changes for elementary school students. This study employed a Research and Development approach involving expert validation and classroom implementation at MIN 4 Banda Aceh. The developed e-book was evaluated by material and media experts, followed by implementation with fourth-grade students. Data were analyzed using descriptive quantitative analysis to determine the feasibility of the e-book and students' scientific literacy across five dimensions. The e-book obtained highly appropriate ratings from media experts (90%) and material experts (91%), indicating that it met the feasibility criteria for classroom use. During classroom implementation, students achieved an overall scientific literacy score of 78.9% (high category). The highest achievement was observed in scientific content knowledge (89.4%) and scientific attitude (81.9%), while comparatively lower scores in scientific process, reasoning, and application in real-world contexts indicate areas requiring further instructional support. The findings suggest that the developed interactive science e-book is a feasible learning resource that supports contextual science learning and the development of students' scientific literacy through the integration of Acehnese local content.